A Long-Range, High-Efficiency Resonant Wireless Power Transfer via Imaginary Turn Ratio Air Voltage Transformer - Hsien-Chung Tang; Chun-Hao Chen; Edward-Yi Chang; Da-Jeng Yao; Wei-Hua Chieng; Jun-Ying He (Energies)
This paper presents a resonant wireless power transfer method that leverages a 90-degree voltage phase shift between the transmitting and receiving coils to enhance efficiency and maximize power transfer. When the resonant coupling is achieved, the secondary coil with an adjustable capacitor forms a tuned LC circuit. If the primary coil is driven at the resonant frequency of both the primary and secondary sides, the system can transmit 250W of power between the coils over a distance of 50 cm. Using a single power transmitting unit (PTU) board with multiple paralleled gallium nitride high-electron-mobility transistors (GaN HEMTs), the system achieves a maximum power transfer efficiency of 88%, highlighting the effectiveness of the design in high-efficiency, long-distance wireless power transmission. The key to the success of high-power, high-efficiency RWPT is in exhibiting the imaginary turn ratio presented on the air transformer. The imaginary turn ratio can realize the negative impedance conversion that converts the positive resistance on the power-receiving unit into a negative one, and thus, the damping of the resonance oscillation becomes negative and positively encourages more power to be delivered to the power-receiving unit (PRU) load. This paper derives the theory of the imaginary turn ratio and demonstrates the implementation of the RWPT system that exhibits the imaginary turn ratio effect.